Exploring the Adaptive Capacity of Coastal Communities to Tsunami Risk: A Systematic Literature Review on Community Resilience, Social Capital, and Local-Based Disaster Mitigation in North Sumatra, Indonesia - Linda Elida (International Journal of Social Sciences and Humanities, 2026)
North Sumatra lies along one of the world’s most seismically active coastlines and remains exposed to tsunami-generating earthquakes more than two decades after the 2004 Indian Ocean tsunami. This article presents a PRISMA-informed systematic literature review of 80 peer-reviewed and indexed publications from 2024 to 2026, retrieved from Scopus, Web of Science, ScienceDirect, and Google Scholar. The review examines how adaptive capacity, community resilience, social capital, and local-based disaster mitigation shape coastal communities’ ability to withstand and recover from tsunami risk. Findings show that adaptive capacity is formed through the interaction of three reinforcing pillars: cognitive and material preparedness, bonding and bridging social capital, and culturally embedded mitigation practices such as the Acehnese Smong narrative. However, resilience outcomes remain weakened by institutional fragmentation, gendered exclusion, and the limited integration of customary knowledge into formal disaster governance, particularly in North Sumatra’s coastal districts. The review proposes a synthesized conceptual framework and concludes that strengthening coastal resilience requires integrating indigenous early-warning knowledge with formal disaster risk reduction systems while expanding inclusive social capital networks for women, older adults, and economically marginalised fishing households.